Study on Parameters Related to Growth, Yield, and Quality of Strawberry Plants (Fragaria vesca L.) Grown Hydroponically and in Soil - Le Thi Thuy; Nguyen Thi Oanh; Nguyen Phuong Thao (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study evaluated the effects of soil and hydroponic cultivation on the growth, yield, and quality parameters of Hana strawberry plants (Fragaria vesca L.). In the hydroponics method, four nutrient solutions were used: an inorganic Hydro Umat F solution, two types of organic solutions (fish-based soluble fertilizer and Vermicompost soluble fertilizer), and a combination of organic and inorganic nutrients (Hydro Umat F solution and Banana soluble fertilizer in a 1:1 ratio). TN1 substrate was combined with additional fertilization of fish- based soluble fertilizer, which was used in the experiment of growing plants in soil. The results showed that hydroponic cultivation using the Hydro Umat F solution promoted better growth than the other three nutrient solutions, and soil. Specifically, strawberry plants grown in the Hydro Umat F solution had the highest number of leaves per plant, stolons per plant and the largest leaflet size in the experimental groups. Conversely, soil cultivation resulted in higher yield and quality of Hana strawberries, as indicated by parameters such as the number of flowers per plant (29.67) flowers, the number of fruits per plant (20.08) fruits, fruiting rate (67.69)%, fresh weight of fruit (16.25 g), vitamin C content (66.7) mg.100g-1 fresh weigh, total organic acid content (159.31) mg.100g-1 fresh weight and sweetness index (11.08) oBrix. The results also showed that hydroponic cultivation with organic solutions reduced the growth and yield of Hana strawberry plants compared to inorganic solutions.